Optimum utilization of quarry dust as partial replacement of sand in green concrete - Abdullah, Jaharatul Dini Karen Lee (2015)
The reduction in the source of natural sand and the requirement for reduction in the cost of concrete production has resulted poor quality sand sources supplied and thus increased need to identify substitute material to sand as fine aggregates in the production especially in concrete. To overcome from this crisis, partial replacement of sand with quarry dust can be economical alternative. Quarry dust, a by-product from the crushing process during the quarrying activities is one of such materials. In the Peninsular of Malaysia there were also been many attempts to use quarry dust as partial replacement but only up to 50% on the lower grades concrete with different construction purposes. This paper present mix design of higher grade 60 that develop with a replacement of 0% (100% of natural sand), 50% and up to a maximum of 70% of quarry dust usage. Tests were conducted on cubes to determine the properties and strength of concrete made of quarry dust and the results were compared with natural sand concrete. An attempt has also been made to conduct the slump test to determine the fresh concrete workability and also to obtain the compressive strength (cubes), spilt tensile strength, flexural strength and water absorption of hardened concrete for laboratory analysis